2021
DOI: 10.51470/plantarchives.2021.v21.s1.118
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bovine Fascioliasis in Hawler Modern Abattoir, Erbil, Kurdistan Region, Iraq

Abstract: Fascioliasis in Iraq is prevalent and causes critical economic losses. The aim of this study were to evaluate and determine the prevalence of bovine fascioliasis in Hawler modern abattoir in Erbil province, Iraq, also to evaluate the host related risk factors on the occurrence of fascioliasis and to access the hematological and biochemical changes in infected animals. Hematological and biochemical parameters of 21 infected cattle were compared with 30 parasitefree cattle. Out of 850 slaughtered cattle in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Climate and other environmental factors, such as the presence of water bodies, wetlands, and pastures, have a significant impact on the distribution of F. hepatica. These elements contribute to the development and transmission of free-living fluke stages by creating an environment that is conducive to the intermediate host's growth and reproduction (Charlier et al, 2011, Relf et al, 2011, Olsen et al, 2015, other relevant factors, such as age, breed, stocking rate, and type of farming system, in addition to climate and environmental factors, are also influencing the likelihood of infection (Fox et al, 2011, Kuerpick et al, 2013, Petros et al, 2013, Caminade et al, 2015, Olsen et al, 2015 Fasciolosis is prevalent in Iraq, and annually causes critical economical losses, in a recent study it was found that the occurrence of fasciolosis in cattle that had been slaughtered was 2.47% in the Erbil province (Ismael and Chalabi, 2021), and 2.30% in the Koya Abattoir that belonging to the Erbil province (Hassan, 2018). Currently, an indirect ELISA technique was used on the serum and milk samples in order to find out how common infections are in small ruminants in the Duhok, Kurdistan Region, Iraq (Mikaeel, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Climate and other environmental factors, such as the presence of water bodies, wetlands, and pastures, have a significant impact on the distribution of F. hepatica. These elements contribute to the development and transmission of free-living fluke stages by creating an environment that is conducive to the intermediate host's growth and reproduction (Charlier et al, 2011, Relf et al, 2011, Olsen et al, 2015, other relevant factors, such as age, breed, stocking rate, and type of farming system, in addition to climate and environmental factors, are also influencing the likelihood of infection (Fox et al, 2011, Kuerpick et al, 2013, Petros et al, 2013, Caminade et al, 2015, Olsen et al, 2015 Fasciolosis is prevalent in Iraq, and annually causes critical economical losses, in a recent study it was found that the occurrence of fasciolosis in cattle that had been slaughtered was 2.47% in the Erbil province (Ismael and Chalabi, 2021), and 2.30% in the Koya Abattoir that belonging to the Erbil province (Hassan, 2018). Currently, an indirect ELISA technique was used on the serum and milk samples in order to find out how common infections are in small ruminants in the Duhok, Kurdistan Region, Iraq (Mikaeel, 2020).…”
Section: Introductionmentioning
confidence: 99%